A New Inexpensive Simulation Model for Ultrasound Assessment of Optic Nerve Sheath Diameter. (20th July 2020) - Johnson, Garrett G. R. J.; Jelic, Tomislav; Derksen, Angela; Unger, Bertram; Zeiler, Frederick; Ziesmann, Markus; Gillman, Lawrence M.
ABSTRACT: Background: Sonographic measurement of optic nerve sheath diameter (ONSD) is becoming increasingly accepted as a diagnostic modality to detect elevations in intracranial pressure. As this technique becomes more widespread, methods to address the inherent operator-dependent nature of this modality will need to be developed. We propose a novel low-cost model to accurately simulate sonographic ONSD measurement for purposes of training and assessment. Methods: We designed models composed of medical tubing of various diameters readily available from typical hospital supplies and suspended them in gelatin. The models were evaluated by ultrasound by three expert point-of-care sonographers using a standard linear array probe and technique proposed in the literature. Results: This model generates faithful simulation of the ONS that closely approximates in vivo images and can be used to produce accurate, reproducible measurements. Materials are low cost and easy to acquire and assemble. Conclusions: Our model provides realistic simulated images of the ONS. Through comparison of sonographic measurements to the known tube diameters, this model serves as a promising inexpensive tool to teach the method of ultrasound assessment of ONSD or as a way to determine accuracy of this novel ultrasound technology.